DIODORUS SICULUS' 'SLAVE WAR' NARRATIVES: WRITING SOCIAL COMMENTARY IN THE BIBLIOTHĒKĒ. (8th November 2018) - Morton, Peter
Abstract : Diodorus Siculus has not enjoyed a positive reputation among historians of antiquity. Since the nineteenth century his Bibliothēkē has been dismissed as a derivative work produced by an incompetent compiler, useful often only in so far as one can mine his text for lost and, evidently, far superior works of history. Diodorus' own input into the Bibliothēkē has been dismissed as the clumsy intervention of 'a small man with pretensions'. In one of the sharpest expressions of the traditional view, Diodorus is not a historian but 'a mere epitomizer and an incompetent one at that'. In recent years voices of dissent have spoken up, determined to investigate Diodorus' own contribution to ancient historiography. Their contributions have been notable for their desire to study and understand Diodorus on his own terms or to problematize his derivative use of his sources. Sacks, in particular, has argued that Diodorus' voice can be heard in nearly every proem, a feature that occurs regularly in the text, and that Diodorus' own views structure his analysis of historical events copied from other authors.